Presentasi Diri Mahasiswa Penghafal Alquran - Raiyati, Siti (Jurnal Studia Insania, 2017)
The Quran, a holy book that guides all Muslims. The Quran is the embodiment of the guidance to bring each individual to the salvation of the world and the hereafter. Everyone has different ways of interacting with the Quran, one of them by memorizing the Quran. Individuals who interact with the Quran by means of memorizing of course have different responsibilities. Teenagers who are Al Quran memorizing students have certain signs in expressing self-presentation that may be different from other teenagers. Using descriptive phenomenology study, there were 4 respondents in this study. The data retrieval technique uses semi structured interviews on the primary and secondary subject and uses nonparticipant observation. The results showed that the four respondents had different self-presentation patterns. The most crucial, the Quran forms interpreted ideals in their self-presentation through the dimensions of the khuluqiyyah dimension with respect to ethical values and the amaliyah dimension pertaining to daily behavior.